Air pollution, well-being, and quality of life in Latin America: a systematic review - Álvarez, Boris; Boso, Àlex; Vallejos-Romero, Arturo (Iberoamerican Journal of Development Studies, 2023)
The aim of this review was to describe the effects of air pollution on well-being and quality of life in Latin American countries, following the systematic methods of the PRISMA-P guidelines. A systematic search of empirical studies published in Web of Science (WoS), Scopus, Scielo and PubMed databases was performed. Thus 17 relevant studies published between 1986 and 2021 were identified: 16 with quantitative designs and 1 a qualitative design. The selected studies were grouped into three thematic approaches: mental health (41 %), negative emotions (35 %) and subjective well-being (24 %). The results indicate that air pollution influences various components of well-being, such as satisfaction with life, subjective well-being, perception of quality of life, symptoms of depression or anxiety, negative emotions such as anguish, annoyance, and frustration, among others. However, there were also multiple empirical gaps to be filled.
Keywords: air pollution; subjective well-being; psychological well-being; emotional distress; Latin America